2018
DOI: 10.1111/obr.12758
|View full text |Cite
|
Sign up to set email alerts
|

The prospective association between objectively measured sedentary time, moderate‐to‐vigorous physical activity and cardiometabolic risk factors in youth: a systematic review and meta‐analysis

Abstract: Summary Sedentary time and moderate‐to‐vigorous physical activity (MVPA) may be uniquely related to cardiometabolic health. Excessive sedentary time is suggested as an independent cardiometabolic risk factor, while MVPA is favourably associated with cardiometabolic health. This systematic review and meta‐analysis summarizes the evidence on a prospective relationship between objectively measured sedentary time, MVPA and cardiometabolic health indicators in youth. PubMed, Embase, CINAHL, PhyscINFO and SPORTDiscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
92
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 93 publications
7
92
0
4
Order By: Relevance
“…Physical activity is associated with improved psychological well-being and lower levels of cardiometabolic risk factors among children and adolescents [1,2]. There is evidence that lower amounts of time spent being sedentary are also associated with improved physical and psychological health among children and adolescents, but it is unclear if these associations are independent of physical activity [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity is associated with improved psychological well-being and lower levels of cardiometabolic risk factors among children and adolescents [1,2]. There is evidence that lower amounts of time spent being sedentary are also associated with improved physical and psychological health among children and adolescents, but it is unclear if these associations are independent of physical activity [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…A large cross-sectional study, including pooled data from 14 studies and 20.871 children and adolescents found favorable levels of waist circumference, systolic blood pressure, insulin, and HDL-C among children and adolescents who spent more time in moderate to vigorous physical activity (MVPA), independent of the amount of time spent sedentary [6]. The evidence from prospective studies also supports a protective association between physical activity (PA), overall sedentary time and cardiometabolic risk-markers in children and youth [7][8][9]. Other modifiable behavioral factors influencing markers of cardiometabolic health during childhood and adolescence include sleep-duration and energy intake [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 96%
“…It is well known that participation in regular physical activity (PA) is important for both physical and mental health [1]. Among adolescents, cross-sectional and prospective studies have reported inverse associations between device measured PA, adiposity and cardiometabolic risk factors [2][3][4]. PA is also associated with mental health, when mental health is restricted to the outcomes of depression, anxiety, self-esteem and cognitive functioning [5,6].…”
Section: Registered' Backgroundmentioning
confidence: 99%